The effects of learning styles and attention control on P300 test in young adults - Sema Satıcı; Yeter Saçlı; Nilüfer Bal; Ayşe Ayça Çiprut; Ali Cemal Yumuşakhuylu; Çağlar Batman (The Egyptian Journal of Otolaryngology)
Abstract Background Learning style is a set of characteristics that an individual uses while perceiving, learning, and reacting. There are basically three types: visual, auditory, and kinesthetic. Attentional control is the capacity of an individual to choose what to pay attention to and what to ignore. P300 is one of the event-related potential responses recorded by recognizing the infrequent stimulus in frequent stimuli. Research indicates that the P300 is associated with the differences in learning and can be utilized alongside standard psychometric assessments for evaluation. The differences between learning styles and attentional control in cortical regions are not yet fully understood. The aim of this study was to evaluate the relationship of different learning styles and attentional control with P300 in normal hearing individuals. Method Forty-nine participants aged 18–30 years normal hearing university-educated individuals were administered P300 test, Maggie McVay Lynch Learning Style Inventory and Attentional Control Scale. One-Way ANOVA or Kruskal–Wallis test was used for comparisons between groups according to data normality, and Pearson or Spearman analysis was used for correlation analyses. Results Although shorter P300 latencies were obtained in auditory learning style subjects and larger P300 amplitudes were obtained in visual learning style subjects, P300 latencies and amplitudes of visual, auditory, and kinesthetic learning style subjects did not differ statistically. In addition, the attention controls of the groups were similar. No significant correlation was found between attentional control and P300 latencies and amplitudes. Conclusion Although some questions in the questionnaires were associated with P300, the presence of different learning styles did not have a significant effect on P300. Furthermore, the level of attentional control was not found to be related to the P300.